Mutations in CDK5RAP2 cause Seckel syndrome. Issue 5 (24th May 2015) - Yigit, Gökhan; Brown, Karen E.; Kayserili, Hülya; Pohl, Esther; Caliebe, Almuth; Zahnleiter, Diana; Rosser, Elisabeth; Bögershausen, Nina; Uyguner, Zehra Oya; Altunoglu, Umut; Nürnberg, Gudrun; Nürnberg, Peter; et al.
Abstract: Seckel syndrome is a heterogeneous, autosomal recessive disorder marked by prenatal proportionate short stature, severe microcephaly, intellectual disability, and characteristic facial features. Here, we describe the novel homozygous splice‐site mutations c.383+1G>C and c.4005‐9A>G in CDK5RAP2 in two consanguineous families with Seckel syndrome. CDK5RAP2 ( CEP215) encodes a centrosomal protein which is known to be essential for centrosomal cohesion and proper spindle formation and has been shown to be causally involved in autosomal recessive primary microcephaly. We establish CDK5RAP2 as a disease‐causing gene for Seckel syndrome and show that loss of functional CDK5RAP2 leads to severe defects in mitosis and spindle organization, resulting in cells with abnormal nuclei and centrosomal pattern, which underlines the important role of centrosomal and mitotic proteins in the pathogenesis of the disease. Additionally, we present an intriguing case of possible digenic inheritance in Seckel syndrome: A severely affected child of nonconsanguineous German parents was found to carry heterozygous mutations in CDK5RAP2 and CEP152 . This finding points toward a potential additive genetic effect of mutations in CDK5RAP2 and CEP152 . Abstract : The study describes two novel homozygous splice‐site mutations in CDK5RAP2 (CEP215) in two consanguineous families with Seckel syndrome, and an additional case with possible digenic inheritance in Seckel syndrome. CDK5RAP2 is essential for centrosomal cohesion and proper spindle formation and has been shown to be causally involved in primary microcephaly. This study establishes CDK5RAP2 as a disease‐causing gene for Seckel syndrome and shows that CDK5RAP2 deficiency results in severe defects in mitosis and spindle organization.